If the above integral above can be expressed as
where and are integers, find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have I = ∫ 0 ∞ x 2 sin x ( 1 − e − x ) d x = = ∫ 0 ∞ x sin x ∫ 0 1 e − x u d u d x ∫ 0 1 ∫ 0 ∞ x sin x e − x u d x d u If we define F ( u ) = ∫ 0 ∞ x sin x e − x u d u , u > 0 , then F ′ ( u ) = − ∫ 0 ∞ sin x e − x u d x = − u 2 + 1 1 , u > 0 , and hence F ( u ) = 2 1 π − tan − 1 u , u > 0 , since F ( u ) converges to 0 as u → ∞ . It is worth observing in passing that the fact that F ( u ) tends to 2 1 π as u → 0 evaluates the infinite integral ∫ 0 ∞ x sin x d x = 2 1 π . Getting back on track, we see that I = = ∫ 0 1 ( 2 1 π − tan − 1 u ) d u = 2 1 π − [ u tan − 1 u ] 0 1 + ∫ 0 1 u 2 + 1 u d u 2 1 π − 4 1 π + [ 2 1 ln ( u 2 + 1 ) ] 0 1 = 4 1 π + 2 1 ln 2 , so that A = 4 and B = 2 , and the answer is 6 .